1993
DOI: 10.1007/bf00159122
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunohistolocalization of carbonic anhydrase isozymes I, II and III in the equine and bovine digestive tract

Abstract: Immunohistochemical localizations of carbonic anhydrase isozymes (CA-I, CA-II and CA-III) in equine and bovine digestive tracts were studied. In the horse, epithelial cells in both the oesophagus and non-glandular part of the stomach lacked all three isozymes. In contrast, surface epithelial and parietal cells in the glandular region of the stomach showed reactivity for CA-II. In the small intestine, absorptive columnar cells covering the villi in the duodenum were positive for CA-II. The epithelium of the jej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…CA-VI was detected in epithelial cells in the upper region of the small and large intestinal glands in addition to CA-II expression [28]. At the small intestinal epithelium, immunoreaction against CA-VI was slight, which suggests that the small intestine may utilize CA-VI for the absorption of amino acids and other nutrient components.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…CA-VI was detected in epithelial cells in the upper region of the small and large intestinal glands in addition to CA-II expression [28]. At the small intestinal epithelium, immunoreaction against CA-VI was slight, which suggests that the small intestine may utilize CA-VI for the absorption of amino acids and other nutrient components.…”
Section: Resultsmentioning
confidence: 97%
“…CA-VI may be used for the control of pH and ion balance at the ruminant upper digestive tract in association with other CA isozymes. CA-VI is also found in various mammalian tissues, such as uterus, prostate and mammary glands in man, mouse, rat, hamster, guinea pig, cow, and horse [12,[28][29][30]. Expression of CA-VI in the bovine stratified epithelial cells at the basal layer in esophagus and forestomach stratified epithelium might assist cytosolic CA isozymes in the absorption of VFAs and ammonia.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the immunohistochemical localization of CA-I, CA-II and CA-III in equine salivary glands [2]. We have also immunohistochemically localized CA isozymes to the equine digestive tract [15], but no previous studies have measured CA-I and CA-II levels in equine erythrocytes.…”
mentioning
confidence: 99%
“…The properties of epithelial cells in digestive tract (including expression of CA isoenzymes) vary according to animal species and region of the tract. CA isoenzymes are widely involved in the functions of the digestive tract, and investigators have reported different patterns of expressions of these enzymes in the digestive organs of cattle [6,14], horses [3], rats [4,7,9] and dogs [5], which represent significant variation in diet. However, no reports to date have investigated such expression in pigs.…”
mentioning
confidence: 99%
“…Carbonic anhydrase (CA) isoenzymes involved in the hydration of carbon dioxide are ubiquitous in the living world [8,[13][14][15][16][17]. In animals, there are at least 5 carbonic anhydrase isozymes: CA-I, CA-II, CA-III, CA-IV, and CA-VI, each with its own molecular structure.…”
mentioning
confidence: 99%